ANALYSIS OF TRANSLATION TECHNIQUE IN THE WEBTOON “SMILE BRUSH” BY WAROO - Salsabela Hasna Rosida; Dyah Nugrahani; Rahmawati Sukmaningrum (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The purpose of this study were (1) to find out the translation techniques used in comics in the webtoon application entitled "Smile Brush" by Waroo and (2) to find out the most dominan translation technique in the webtoon entitled "Smile Brush" by Waroo .This study is used descriptive qualitative method to analyze and describe the translation technique used in Webtoon entitled “Smile Brush” by Waroo. The data in this study were collected through webtoon application. The source of this study was the original text of the webtoon in Indonesian (Source Language) translated into English (Target Language) by fans of the webtoon. To collect data, the researcher used a random sampling technique. From 36 episodes on the webtoon, the researcher took 10% of the data. The researcher analyzed what technique the translator used in translating the webtoon based on the translation technique put forward by Molina and Albir (2002). From this study, the writer presented two points of the results of the study. First, the translation technique used in the Webtoon entitled "Smile Brush" by Waroo is literal (36.8%), established equivalent (27.9%), reduction (20.6%), borrowing (2.9%), amplification (1.5%), and transposition (1.5%). In addition, in the second point it can be concluded that the most dominant translation technique used in the Webtoon entitled "Smile Brush" by Waroo is a literal translation (36.8%)